Activating the desire to learn - Sullo, Robert A., 1951- (Association for Supervision and Curriculum Development, 2007)
Written as a series of candid dialogues between the author and K-12 students, teachers, counselors, and administrators, Activating the Desire to Learn shows how to apply lessons from the research on motivation to classroom instruction.